Mindfulness-based Cognitive Therapy (MBCT) in bipolar disorder: preliminary evaluation of immediate effects on between-episode functioning. - Williams, J; Alatiq, Y; Crane, C; Barnhofer, T; Fennell, M; Duggan, D; Hepburn, S; Goodwin, G (2008)
BACKGROUND: Bipolar disorder is highly recurrent and rates of comorbidity are high. Studies have pointed to anxiety comorbidity as one factor associated with risk of suicide attempts and poor overall outcome. This study aimed to explore the feasibility and potential benefits of a new psychological treatment (Mindfulness-based Cognitive Therapy: MBCT) for people with bipolar disorder focusing on between-episode anxiety and depressive symptoms. METHODS: The study used data from a pilot randomized trial of MBCT for people with bipolar disorder in remission, focusing on between-episode anxiety and depressive symptoms. Immediate effects of MBCT versus waitlist on levels of anxiety and depression were compared between unipolar and bipolar participants. RESULTS: The results suggest that MBCT led to improved immediate outcomes in terms of anxiety which were specific to the bipolar group. Both bipolar and unipolar participants allocated to MBCT showed reductions in residual depressive symptoms relative to those allocated to the waitlist condition. LIMITATIONS: Analyses were based on a small sample, limiting power. Additionally the study recruited participants with suicidal ideation or behaviour so the findings cannot immediately be generalized to individuals without these symptoms. CONCLUSIONS: The study, although preliminary, suggests an immediate effect of MBCT on anxiety and depressive symptoms among bipolar participants with suicidal ideation or behaviour, and indicates that further research into the use of MBCT with bipolar patients may be warranted.